Data security model using deep learning and edge computing for Internet of Things (IoT) in smart city - Aziz, Md. Yasin; Kabbo, Tanjid Alam; Tahsin, Tasnuva; Zumme, Nadia Haque; Tahsin, Mohammad Sadman (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.